Manufacturing and Morphological Analysis of Composite Material of Polystyrene Nanospheres/Cadmium Metal Nanoparticles - Hadi Nur; Pratama Jujur Wibawa; Hashim Saim; Mohd. Arif Agam (Bulletin of Chemical Reaction Engineering & Catalysis, 2013)
A very simple nanocomposite material has been in-situ manufactured from an aqueous polystyrene nanospheres dispersion and cadmium (Cd) metal nanoparticles. The manufacturing was performed by using a high frequency of 40 kHz ultrasonic (US) agitation for 45 minute at atmospheric pressure and at room temperature 20 oC. No chemical reducing agent and surfactant added in this manufacturing technique due to the US could reduce Cd2+ ions of cadmium nitrate tetrahydrate to Cd atomic metals nanoparticles whereas water molecules could act as a pseudo stabilizer for the manufactured material. A thin film was manufactured from aqueous colloidal nanocomposite material of Polystyrene nanospheres/Cd metal nanoparticles (PSNs/CdMNp) fabricated on a hydrophilic silicon wafer. The thin film was then characterized by a JEOL-FESEM for its surface morphology characteristic and by ATR-FTIR spectrometry for its molecular change investigation. It could be clearly observed that surface morphology of the thin film material was not significantly changed under 633 nm wavelength continuous laser radiation exposure for 20 minute. In addition, its ATR-FTIR spectra of wave number peaks around 3400 cm-1 have been totally disappeared under the laser exposure whereas that at around 699 cm-1 and 668 cm-1 have not been significantly changed. The first phenomenon indicated that the hydrogen bond existed in PSNs/CdMNp material was collapsed by the laser exposure. The second phenomena indicated that the PSNs phenyl ring moiety was not totally destroyed under the laser exposure. It was suspected due to the existence of Cd nanoparticles covered throughout the spherical surface of PSNs/CdMNp material particles. Therefore a nice model of material structure of the mentioned PSNs/CdMNp nanocomposite material could be suggested in this research. It could be concluded that this research have been performed since the material structure model of the manufactured PSNs/CdMNp nanocomposite could be drawn and proposed. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)(Selected Paper from International Conference on Chemical and Material Engineering (ICCME) 2012)